Electrical and Magnetic Properties of Graphene Films with Ni Nanoparticles. (2015) - Okhay, Olena; Guerra, Luis M.; Ventura, João; Tkach, Alexander; Kläui, Mathias; Krishna, Rahul; Titus, Elby
Abstract: Electrical properties and magnetic properties of graphene oxide and reduced graphene oxide films with addition of Ni nanoparticles were investigated. It is found that reduction of GO by Hydrazine hydrate (HH) and subsequent mixing with Ni NPs yields a higher current (10 -5 A) compared to the samples where GO is first mixed with Ni NPs and further reduced (10 -6 A). At the same time, GO sample prepared by addition of Ni NPs to GO with subsequent reduction by HH presents the largest hysteresis with Mr as high as 11.8emu/g. Moreover, mixing of Ni NPs with HH before addition to GO or addition of Ni NPs to already reduced GO yields smaller values of the magnetization. Thus, the optimal procedure to obtain the magnetic response requested for particular application can be chosen.